Clasificación y perspectivas metodológicas de la previsión económica - Rodríguez Meitín, Benigno (1956)
Following the path opened by PIATIER (France), LANGELÜTRE (Germany) and TAGLIACARNE (Italy), the author reviews the various methods of business cycle forecasting: barometers, abstract models, economic accountancy, test, etc. and tries to classify then systematically. He arrives at the conclusion that none of them could be considered as exclusive, which does not mean though that they have to be discarded either, each one of them having at least a relative value and a limited field of application, these being determined by circumstances and the aims followed, limits which the author tries to outline, using the tests as the central axis do investigation and considering all the other methods as being merely complementary.